Aquaculture-induced boundary circulation and its impact on coastal frontal circulation. (28th May 2019) - Xuan, Jiliang; He, Yuqing; Zhou, Feng; Tang, Cheng; Zheng, Xiangyang; Liu, Hui; Yu, Liangju; Chen, Jianfang
Abstract: With the development of coastal suspended aquaculture industry, aquaculture facilities have extended into the open sea to depths of up to 30 m. This practice will likely affect the natural ocean circulation in such areas. For a case study in the high-density aquaculture region of the coastal Yellow Sea, an aquaculture-induced boundary circulation (ABC) is identified and its effects on the background frontal circulation and cross-shore nutrient supply are examined. The ABC is composed of a southward along-boundary current and a counterclockwise cross-boundary cell. The southward along-boundary current (∼5 cm s −1 ) along with the natural frontal current (∼5 cm s −1 ) forms a strong coastal current (∼10 cm s −1 ) along 20–30 m isobaths. The counterclockwise cross-boundary cell exhibits the opposite direction to the natural clockwise cross-frontal cell in the frontal area, which reduces the cross-shore nutrient supply by nearly 25%. Our results suggest that aquaculture boundaries and densities should be considered when planning high-density aquaculture activities.